Marriage of convenience. 3 - Ken; Ken; Hanheun (Ize Press, 2026)
Bianca and Zachary are closer than ever before-but her husband isn't the only man who is taken by her! Not only is the future tyrant, Prince Jacob, inexplicably drawn to Bianca, but her former minstrel lover also sets his sights on the lovely countess. Can the married couple's fragile, new relationship withstand all these unexpected obstacles?